The complex implementation of new biotechnologies for the rehabilitation of natural ecosystems as a tool for implementing sustainable development of regional rural territories - Pytkin, A.; Tarasov, M.; Balandin, D. A. (Perm Federal Research Centre Journal, 2013)
The article considers the issues of improving the mechanism and instruments to reduce the negative anthropogenic impact on the environment and rehabilitation of Perm Krai’s rural territories natural ecosystems. The authors reveal the complex implementation of new biotechnologies, allowing to involve the wastes of the agricultural production and the timber industrial complex in a new production cycle as a materials source for recultivating agricultural lands and restoring industrially polluted natural objects and soils.